Güzîdeî-yi isnâd-ı siyâsi-yi İrân ve Osmânî (Tahran Tahran Tahran Tahran)
7 cilt (1. c. [9], 879 sayfa, [7] sayfa resim, harita ; 2. c. [9], [22], 753 sayfa, [1] yaprak harita ; 3. c. [16] s., 801 sayfa ; 4. c. [15], 596 sayfa ; 5. c. [32], 579 sayfa ; 6. c. [35], 720 sayfa ; 7. c. [50], 867, [1] sayfa)